2017
DOI: 10.1002/smll.201604261
|View full text |Cite
|
Sign up to set email alerts
|

Precise Patterning of Organic Single Crystals via Capillary‐Assisted Alternating‐Electric Field

Abstract: Owing to the extraordinary properties, organic micro/nanocrystals are important building blocks for future low-cost and high-performance organic electronic devices. However, integrated device application of the organic micro/nanocrystals is hampered by the difficulty in high-throughput, high-precision patterning of the micro/nanocrystals. In this study, the authors demonstrate, for the first time, a facile capillary-assisted alternating-electric field method for the large-scale assembling and patterning of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Recently, the surface microstructure–assisted patterning method was also extended for the formation of patterned 0D organic crystals. Zhang et al reported an alternating‐electric field (AEF)‐based method, which is schematically shown in Figure a. Aqueous dispersion of organic crystals was injected into a tilted cell, which consisted of two parallel pieces of conductive indium–tin oxide (ITO) glasses.…”
Section: Patterning Of Organic Semiconductor Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the surface microstructure–assisted patterning method was also extended for the formation of patterned 0D organic crystals. Zhang et al reported an alternating‐electric field (AEF)‐based method, which is schematically shown in Figure a. Aqueous dispersion of organic crystals was injected into a tilted cell, which consisted of two parallel pieces of conductive indium–tin oxide (ITO) glasses.…”
Section: Patterning Of Organic Semiconductor Crystalsmentioning
confidence: 99%
“…g,h) SEM images of the 0D and 1D organic crystal–based device arrays. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Patterning Of Organic Semiconductor Crystalsmentioning
confidence: 99%
“…Solution-processed organic field-effect transistors (OFETs) have received considerable attention because of their attractive features of superior intrinsic mechanical flexibility, dramatic performance improvement, and compatibility with low-cost printing processes. These fascinating features of OFETs make them ideal candidates for applications such as flexible display backplanes, sensors, radio frequency identification tags, smart memory, and wearable electronic systems. Over the past few decades, apart from developing high-mobility organic semiconductors, researchers have focused on developing low-cost solution-based processes for OFETs using various printing techniques (e.g., doctor-blade coating, bar coating, inkjet printing, and dip-coating). These techniques have been optimized to yield polymer thin films with uniform and smooth morphologies and desirable crystal structures that ensure efficient charge transport in OFETs. , …”
Section: Introductionmentioning
confidence: 99%
“…In the first type, the driving force for organizing materials arises mainly from π-π van der Waals interactions among conjugated organic molecules. The second type takes advantage of both π-π and external interactions, such as mechanical forces [15] and capillary force [16]. The former is governed in the case of physical vapor deposition.…”
Section: Introductionmentioning
confidence: 99%